THE FOUNDATIONS OF THE SUBJECTS OF CRIME UNDER SHARĪʿA - Khakimova Nigora (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the foundations of the subject of crime in Sharīʿa. It discusses the age of responsibility, mental soundness, and the role of coercion in determining criminal responsibility under Islamic law. A key point of the article is that a person cannot be regarded as the subject of a crime if the act was committed under coercion. The views presented in the article are supported by relevant verses of the Qurʾān and the Sunna.